Saber e sabor: corpo, medicina e cozinha na obra de Francisco da Fonseca Henriques - Luca Palmesi (2014)
The present work is a study about the medical thought in the works of the portuguese Francisco da Fonseca Henriques (1665-1731), King D. João Vs doctor (1689-1750). The main works analised are Medicina Lusitana (1710), the Dissertação dos humores naturais do corpo humano (1715), the Âncora Medicinal (1721) and the Aquilégio Medicinal (1731). Specially the Âncora was utilized as a fagot of several textual and cultural references of the western medical thought, from which it has tryed to discuss the basis of the main medical wings of the period known as the Scientific Revolution going back to its ancient and medieval sources. Aswell the relations of great proximity and communication between the erudit and popular thought, mediated by the common language of sensitive experience, mainly to what concerns the central relationship between food and health. The study tryes to explore the way opened by the crossroad between history of medical thought and history of food.